EVALUATION OF SOLID WASTE IN A LANDFILL BY MEANS OF THE QUALITY INDEX - Lima, P. G.; Tamarindo, U. G. F.; Forti, J. C.; Braga Junior, S. S. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Effective operation and management of a landfill is essential if solid waste is to be properly disposed of at the final disposal stage, thereby giving priority to public health and environmental protection. In this context, the present work tries to technically evaluate a solution of solid urban waste in a certain sanitary landfill located in a small municipality in the countryside of the State of São Paulo (CETESB). An evaluation was carried out using the waste quality index, according to a methodology implemented by the Environmental Company of the State of São Paulo. It is therefore a case study, whose main objective is to verify how the management of a given municipal landfill is in fact, from the perspective of the waste quality index. The relevance of this study, in turn, is mainly based on the fact that it is verified, as well as supervised, in the delimited geographical area, if the environmental legislation has in fact been observed by the municipality, as well as, from the practical point of view, If the landfill has been correctly used, and not only become a mere "dumping area" and, consequently, generating pollutants with the potential to contaminate soil and water.